Spanish Sme’s In Latin America: Export Barriers (2019)
The main aim of this article is to check if the relative importance attributed to the different export barriers varies as a function of the firm’s export destination. To reach that goal, we analyzed 463 responses from a population of small and medium enterprises, through a dimensionality reduction procedure to composite factors, from a list of 26 possible individual barriers, obtained after reviewing the existing literature on export barriers. Factor analysis with Varimax rotation was used. Results for the region are compared with those to other destination markets in the European Union, Africa and the rest of the world. And the results confirm partially, the existence of differences of export barriers perceptions as a function of the firm’s export destination. Some results from individual barriers are also described.